Androgen receptor inhibits epithelial–mesenchymal transition, migration, and invasion of PC-3 prostate cancer cells. Issue 1 (1st December 2015) - Huo, Chieh; Kao, Yung-Hsi; Chuu, Chih-Pin
Abstract: Bone metastasis is very common in prostate cancer (PCa) and causes severe pain. PC-3 is an androgen receptor (AR)-negative PCa cell line with high metastatic potential established from PCa bone metastasis. We observed that re-expression of AR, which is located in the cytoplasm in the absence of androgen, suppressed cell motility, migration, and invasion of PC-3 cells as determined by wound healing assay and transwell assay. Micro-Western Array and Western blotting analysis indicated that re-expression of AR increased APC, Akt2, Akt3, PI3K p85, phospho-PI3K p85 Tyr458, PI3K p85, and E-cadherin but decreased GSK-3β, phospho-GSK-3β Ser9, phospho-mTOR Ser2448, Skp2, NF-κB p50, Slug, N-cadherin, β-catenin, vimentin, MMP-9, and Snail. Migration and invasion of PC-3 and PC-3 AR cells were promoted by EGF or IGF-1 but were suppressed by Casodex. Re-expression of AR reduced the activity of MMP-2 and MMP-9 in PC-3 cells. Our observations suggested that re-expressing AR suppresses migration and invasion of PC-3 cells via regulation of EMT marker proteins and MMP activity.